2009
DOI: 10.1051/0004-6361/200912361
|View full text |Cite
|
Sign up to set email alerts
|

Destriping CMB temperature and polarization maps

Abstract: We study destriping as a map-making method for temperature-and-polarization data for cosmic microwave background observations. We present a particular implementation of destriping and study the residual error in output maps, using simulated data corresponding to the 70 GHz channel of the Planck satellite, but assuming idealized detector and beam properties. The relevant residual map is the difference between the output map and a binned map obtained from the signal + white noise part of the data stream. For des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 35 publications
(49 reference statements)
3
51
0
Order By: Relevance
“…At 30 GHz the 1/ f noise is higher than measured on the ground, with a knee frequency of about 100 mHz. Residual fluctuations in the timestreams, however, are effectively removed during map-making, as expected from several pre-launch simulation studies (Kurki-Suonio et al 2009;Poutanen et al 2004;Keihänen et al 2004). We have shown that the noise increase due to the 1/ f component is a few percent at 30 and 44 GHz, and only 0.2% at 70 GHz.…”
Section: Discussionsupporting
confidence: 74%
“…At 30 GHz the 1/ f noise is higher than measured on the ground, with a knee frequency of about 100 mHz. Residual fluctuations in the timestreams, however, are effectively removed during map-making, as expected from several pre-launch simulation studies (Kurki-Suonio et al 2009;Poutanen et al 2004;Keihänen et al 2004). We have shown that the noise increase due to the 1/ f component is a few percent at 30 and 44 GHz, and only 0.2% at 70 GHz.…”
Section: Discussionsupporting
confidence: 74%
“…For Planck's actual scan strategy, scan circle crossings at substantial angles occur over about ±20 • around the poles, so that a much longer run of the circle is involved in constraining the offsets, giving higher signal to noise, and also reducing the sensitivity to monopole-dipole degeneracy. The actual determination of the offsets will be made in the course of iterative destriping, for instance using the madam algorithm (Keihänen et al 2005;Keihänen et al 2010;Ashdown et al 2007;Kurki-Suonio et al 2009). …”
Section: Zero Levels and Destripingmentioning
confidence: 99%
“…The first term on the rhs is the binned white noise contribution (a diagonal or block-diagonal matrix for temperature-only and polarized cases respectively) and the second term describes the pixel-pixel correlations due to errors in solving for the baselines, i.e., the difference between the solved and actual baselines (Kurki-Suonio et al 2009). When making a map using destriping, one can use high resolution to solve for baselines and still bin the map at low resolution.…”
Section: Destriped Map Covariancementioning
confidence: 99%